Cold mountain stream chironomids (Diptera) of the genus Diamesa indicate both historical and recent climate change - Dočkalová, Kateřina; Stuchlík, Evžen; Hamerlík, Ladislav; Bitušík, Peter; Turek, Jan; Svitok, Marek; Novikmec, Milan; Lackner, Reinhard; Dvorak, Martin; Kopáček, Jiří; Tátosová, Jolana; Camarero, Lluís; et al. (Environmental entomology, 2024)
Chironomids of the genus Diamesa (Meigen, 1835, Diptera: Chironomidae) inhabit cold, oxygen-rich running waters. We have investigated the presence of Diamesa and other freshwater macroinvertebrates at 22 stream sampling sites in 3 European high mountain regions (the Central Pyrenees, the Ötztal Alps, and the Tatra Mountains) to establish suitable temperature conditions for Diamesa dominance. It has been generally accepted that their high abundance was linked to the presence of glaciers; however, we have shown that in the Tatra Mountains, where there are no glaciers, the conditions for the dominance of Diamesa species are created due to permanent snowfields, the geographical orientation of the valley and shading by the surrounding high peaks. The historical connection of Diamesa to glaciers was investigated from the paleolimnological records of subfossil chironomid assemblages from the Bohemian Forest, where glaciers disappeared before or during the Late Glacial period. As expected, water temperature seems to be the main driver of Diamesa distribution, and we determined that the relative abundance of Diamesa species was significantly higher at the sites with a mean July water temperature below 6.5 °C. The Diamesa-dominated stream communities seems to be endangered due to ongoing climate warming and this assumption is supported by our paleolimnological results from the Bohemian Forest lakes, where Diamesa has disappeared due to warming of lake inflows at the beginning of the Holocene. These findings strengthen the former suggestions that some Diamesa species could be used as an indicator for tracking recent environmental changes in vulnerable ecosystems of cold mountain streams.
Keywords: klimatické změny; Rivers; glacier retreat; Bohemian Forest; nízká teplota; řeky; Pyrenees; Animals; Climate Change; rozšíření zvířat; zvířata; Animal Distribution; Alps; Tatra Mountains; snowfield/glacieret; Cold Temperature; Chironomidae